Effects of LLLT in combination with bisphosphonate on bone healing in critical size defects: A histological and histometric study in rat calvaria - Garcia, Valdir Gouveia [UNESP]; Da Conceição, Juliana Mendonça [UNESP]; Fernandes, Leandro Araújo [UNESP]; Almeida, Juliano Milanezi de [UNESP]; Nagata, Maria José Hitomi [UNESP]; Bosco, Álvaro Francisco [UNESP]; Theodoro, Letícia Helena [UNESP] (Springer Nature, 2013)
The purpose of this study was to analyze histologically the effect of low-level laser therapy (LLLT) in combination with bisphosphonate on bone healing in surgically created critical size defects (CSD) in rat calvaria. One hundred Wistar female rats sham operated (sham) and ovariectomized (Ovx) were maintained untreated for 1 month to allow for the development of osteopenia in the Ovx animals. A CSD was made in the calvarium of each rat, and the animals were divided into five groups according to following treatments: (1) sham rats (control), (2) Ovx rats, (3) Ovx rats treated with LLLT, (4) Ovx rats treated with bisphosphonate, and (5) Ovx rats treated with bisphosphonate and LLLT. Groups 4 and 5 were irrigated with 1 ml of bisphosphonate, and groups 3 and 5 were submitted to LLLT (GaAlAs), 660 nm, 24 J, and 0.4285 W/cm2 on the CSD. Ten animals of each treatment were killed at 30 and 60 days. Histomorphometric assessments, using image analysis software, and histological analyses were performed. No defect was completely regenerated with the bone. Histometrically, it can be observed that groups 3 (37.49 ± 1.94%, 43.11 ± 2.39%) and 5 (35.05 ± 1.57%, 41.07 ± 1.89%) showed a significant bone neoformation when compared to groups 1 (16.81 ± 1.57%, 27.54 ± 1.49%), 2 (11.68 ± 0.98%, 22.51 ± 1.05%), and 4 (14.62 ± 1.70%, 25.67 ± 1.41%) in all experimental periods (P < 0.05). It was possible to conclude that the LLLT associated or not with bisphosphonate treatment was effective for stimulating bone formation in CSD in the calvaria of rats submitted to ovariectomy. © 2012 Springer-Verlag London Ltd.
Keywords: Alendronate; Bisphosphonate; Bone regeneration; Laser therapy; Rats; alendronic acid; bisphosphonic acid derivative; animal cell; animal experiment; animal model; animal tissue; bone defect; bone regeneration; calvaria; controlled study; disease severity; experimental study; female; fracture healing; histometry; histopathology; low level laser therapy; nonhuman; ossification; osteopenia; priority journal; rat; therapy effect; treatment response; Wistar rat